Successful Management of a Rare Case of Dystocia in a Goat due to Ventro-Lateral Abdominal Hernia of Gravid Uterus - Singh, Bhoopendra; Kumar, Rajesh; Singh, Shubhendra Vikram; Singh, Narendra (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Dystocia or difficult birth, a condition in small ruminants (sheep and goat), results in huge economic losses to farmers either due to death of new born(s) or dam and adversely affects dam fertility (Mcsporran, 1980). In goat, the incidence of dystocia is low (Bhattacharyya et al.2015). Obstetrical problems in goats are similar to those in sheep (Majeed, 1994), however, the incidence of dystocia is considered higher in goats compared to ewes (Mehta et al., 2002). Hernia of the gravid uterus occasionally occurs during advanced pregnancy in ruminants usually to the right side of the abdominal floor (Roberts, 1971), leading to dystocia (Oehme and Prier, 1974). Ventral abdominal hernia occurs mainly due to any trauma such as a kick, blow, horn thrust or falling on blunt objects or automobile accidents (Radhakrishnan et al., 1993) and rupture of prepubic tendon (Frank, 1981; Arthur, 1989). The condition is generally observed in pluriparous small ruminants in advanced pregnancy with multiple fetuses, which leads to fragility of abdominal muscles or prepubic tendon (Vijayanand et al., 2012). This paper presents successful management of a rare case of dystocia in a goat due to ventro-lateral abdominal hernia of gravid uterus.